2012
DOI: 10.1159/000338193
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Cancer Imaging

Abstract: Cancer is rapidly becoming the worldwide leading cause of premature death. Iconographic techniques have traditionally provided information on tumor anatomy. The recent introduction of functional and molecular imaging techniques allows probing tumor physiology and biology in addition to mere anatomical description. In addition to the research implications, these novel imaging techniques offer early response assessment and target visualization which, in the era of personalized medicine, may offer significant adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
3
0
1
Order By: Relevance
“…This non-ionizing imaging technique provides to the surgeons, in a real-time manner and at a high signal-to-noise ratio (SNR), sensitive molecular information that optimizes tumor resection and thus the patient's health and life quality. For instance, conventional endoscopy has been coupled with fluorescent imaging probes, increasing the early diagnosis of colorectal cancers [33]. To the best of our knowledge, no optical imaging procedure has yet been proposed for thyroid cancer, although its anatomical accessibility would qualify this pathology as an ideal candidate.…”
Section: Introductionmentioning
confidence: 99%
“…This non-ionizing imaging technique provides to the surgeons, in a real-time manner and at a high signal-to-noise ratio (SNR), sensitive molecular information that optimizes tumor resection and thus the patient's health and life quality. For instance, conventional endoscopy has been coupled with fluorescent imaging probes, increasing the early diagnosis of colorectal cancers [33]. To the best of our knowledge, no optical imaging procedure has yet been proposed for thyroid cancer, although its anatomical accessibility would qualify this pathology as an ideal candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that multitasking diagnostics that combine techniques such as PET (positron emission tomography) and MRI (magnetic resonance imaging) could be really improved if effective multimodal contrast agents exist . The fact that PET images provide functional information about the disease with high sensitivity speeds up the development of clinical PET and hybrid PET/computed tomography (CT) cameras. Although PET imaging provides information about physiological and pathophysiological processes, such a technique is limited by the low anatomical resolution .…”
Section: Introductionmentioning
confidence: 99%
“…Another MRI imaging model for liver regeneration could reliably and reproducibly quantify the proliferative rate of hepatocytes using MRI in rodents [11]. MRI plays an important role in the molecular and functional imaging of cancer [12]. Our group has published interesting results for noninvasive monitoring of tumor growth in a murine model for pancreatic cancer [13] and for tumor growth of pancreatic cancer following surgical trauma [14].…”
Section: Discussionmentioning
confidence: 99%